The perceptions and priorities of professionals in health and social welfare and city planning for creating a healthy living environment: a concept mapping study - Kristine Mourits; Koos van der Velden; Gerard Molleman (BMC, 2021)
Abstract Background It is helpful for collaboration if professionals from the field of health and social welfare and the field of city planning are aware of each other's concepts of what a healthy living environment entails and what its components are. This study examined perceptions about creating a healthy living environment of professionals from these two fields, as well as the differences between them. Methods We recruited 95 professionals from Nijmegen, the Netherlands who worked in the fields of health, social welfare and city planning in governmental and non-governmental capacities. We used the concept mapping method to collect and analyse their thoughts on healthy living environments. Participants first submitted statements on this subject in a brainstorming session, using an online mapping tool. Then they sorted these statements and rated them on priorities and opportunities within urban planning processes. Results During the brainstorm, 43 professionals generated 136 statements. After the elimination of duplicates, 92 statements were individually sorted by 32 professionals. Concept mapping software was used to create an overall map, in which the statements were sorted into ten clusters. Each of these clusters represented one of the main features of a healthy living environments. After 36 participants rated these statements, it emerged that professionals from both fields agreed on priorities and opportunities for the clusters 'Spatial quality' and 'Conducive to exercise'. Professionals also agreed on which three clusters had the fewest priorities and possibilities ('Promotes personal wellbeing', 'Encourages healthy choices', 'Conducive to social connections'). Conclusion We found that professionals in health and social welfare and city planning have similar views concerning the most and least important features of a healthy living environment in urban planning process. This could indicate that the differences between the two fields may be more nuanced and specific than previously thought. This knowledge offers perspectives for professionals to strengthen their collaboration and to come to a joint result in urban planning projects.